Declining farm productivity and profitability due to soil degradation in rice-wheat cropping system – A case study from North India - K, Thimmappa; Singh, Yashpal; R, Raju; Tripathi, Ram Shankar; Kumar, Sandeep; R, Sendhil; Mitrannavar, Dattupant (Journal of Cereal Research, 2015)
Alkali soils are an important category of salt-affected soils and present predominantly in the Indo-Gangetic plains of Northern India. Soil alkalinity and other forms of land degradation reduce the productivity of the crop as well as the farm household income. The purpose of the study is to measure the adverse effect of soil alkalinity on crop production and its’ consequent impact on farm income. The study observed a substantial reduction in the crop productivity and farm income.  The farm income decreased with increase in soil alkalinity level. The annual potential and actual losses per ha were Rs. 10714 and Rs. 7737, respectively, due to the adverse effects of soil alkalinity. It is suggested that these lands should be reclaimed on priority basis to improve soil productivity, farm income and livelihood security of resource-poor farmers.